Using newspapers in English language classrooms in rural secondary schools - Kunek, Andrew (Kota Samarahan : Universiti Malaysia Sarawak, 2002)
This study attempted to investigate the reasons for employing and not employing newspapers in English language classrooms in Rural Secondary Schools. This study also attempted to find the methodologies of using newspaper in English Language classrooms by English Language teachers. The study involved 30 English Language teachers from four selected rural secondary schools in Serian District.